2021
DOI: 10.3390/s21217149
|View full text |Cite
|
Sign up to set email alerts
|

On–Off Scheduling for Electric Vehicle Charging in Two-Links Charging Stations Using Binary Optimization Approaches

Abstract: In this study, we deal with the problem of scheduling charging periods of electrical vehicles (EVs) to satisfy the users’ demands for energy consumption as well as to optimally utilize the available power. We assume three-phase EV charging stations, each equipped with two charging ports (links) that can serve up to two EVs in the scheduling period but not simultaneously. Considering such a specification, we propose an on–off scheduling scheme wherein control over an energy flow is achieved by flexibly switchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The electric machine allows the vehicle's kinetic energy to be recovered during braking. A vehicle with such a system is equipped with a battery with a larger capacity [13][14][15].…”
Section: Factors Influencing the Dynamic Characteristics Of Car Controlmentioning
confidence: 99%
“…The electric machine allows the vehicle's kinetic energy to be recovered during braking. A vehicle with such a system is equipped with a battery with a larger capacity [13][14][15].…”
Section: Factors Influencing the Dynamic Characteristics Of Car Controlmentioning
confidence: 99%
“…To tackle the impracticality, Schoot Uiterkamp et al [23] presented an efficient scheduling algorithm that allows only charging above a given minimum threshold. Zdunek et al [37], in their modeling, included binary variables to indicate whether the EV is charging or not, which can potentially include the minimum charging power in the modeling. Besides traditional modeling, recent literature has successfully applied model-free reinforcement learning (RL) to EV smart charging, where the action space of the RL agent often avoids charging power allocation below the minimum charging power.…”
Section: A Related Workmentioning
confidence: 99%
“…either 0 or in the range [P min , P max ]. Similar to [37], this paper utilizes extra binary decision variable s ∈ B N K×1 to constrain charging power variables by:…”
Section: A Ideal Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Zdunek et al. [ 26 ] developed a scheduling scheme via the binary linear programming. They concluded that the binary linear programming does not enforce the smoothness of the considered scenarios and the scheduling issues of EVs are still open for further future studies.…”
Section: Introductionmentioning
confidence: 99%